2021
DOI: 10.1002/marc.202100136
|View full text |Cite
|
Sign up to set email alerts
|

Phototunable Cloud Point Temperatures Stemming from Cyclic Topology: Synthesis and Thermal Phase Transition Behavior of Cyclic Poly(N‐acryloylsarcosine methyl ester)

Abstract: Cyclic polymers possess distinct properties compared with their linear counterparts, such as smaller hydrodynamic volume, lower viscosity, and higher glass‐transition temperature, etc. To explore the impact of the cyclic topology on the thermo‐induced phase transition behavior of poly(N‐acryloylsarcosine methyl ester) (PNASME), the anthracene‐terminated telechelic PNASMEs are synthesized by reversible addition‐fragmentation chain transfer (RAFT) polymerization of monomer NASME using a bifunctional chain transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Conversely, other studies have reported that cyclic polymers tend to have a higher cloud point than linear polymers. 122–125 There are two possible reasons. First, this is attributed to hindered intermolecular connectivity at the topological level, resulting in repulsive forces between cyclic polymers.…”
Section: Effects Of Different Macromolecular Architectures On Solutio...mentioning
confidence: 99%
“…Conversely, other studies have reported that cyclic polymers tend to have a higher cloud point than linear polymers. 122–125 There are two possible reasons. First, this is attributed to hindered intermolecular connectivity at the topological level, resulting in repulsive forces between cyclic polymers.…”
Section: Effects Of Different Macromolecular Architectures On Solutio...mentioning
confidence: 99%
“…The competing intramolecular click reaction forming the cyclic product can be undesired, and careful reaction optimization would be required. , However, cyclic polymers also have unique physical properties , and similarly minimizing the intermolecular step-growth reaction can be desirable in some cases. For instance, cyclic polymers have lower hydrodynamic volumes, lower intrinsic viscosities, are less susceptible to degradation , and demonstrate different cloud point temperatures to their linear counterparts . Furthermore, they provide a promising biointerface that typically produces a denser and thicker surface film compared to linear equivalents .…”
Section: Introductionmentioning
confidence: 99%